2017
DOI: 10.7554/elife.21012
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic transcription factor expression in mice predicts medial amygdala neuronal identity and sex-specific responses to innate behavioral cues

Abstract: The medial subnucleus of the amygdala (MeA) plays a central role in processing sensory cues required for innate behaviors. However, whether there is a link between developmental programs and the emergence of inborn behaviors remains unknown. Our previous studies revealed that the telencephalic preoptic area (POA) embryonic niche is a novel source of MeA destined progenitors. Here, we show that the POA is comprised of distinct progenitor pools complementarily marked by the transcription factors Dbx1 and Foxp2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(108 citation statements)
references
References 67 publications
13
87
0
Order By: Relevance
“…We previously revealed that the embryonically expressed transcription factors, Dbx1 and Foxp2, define different embryonic progenitor pools that are destined to generate two molecularly and electrophysiologically distinct subclasses of mature MeA inhibitory output neurons. We have further shown that MeA Dbx1-lineage and Foxp2-lineage neurons respond in a sex and lineage-specific manner to aggressive, defensive, or mating cues (Lischinsky et al, 2017). Understanding both sex and lineage-specific differences in neuronal biophysical properties is a critical step to ultimately understand how different neuronal populations in the male and female MeA processes sensory information for appropriate behavioral outputs.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…We previously revealed that the embryonically expressed transcription factors, Dbx1 and Foxp2, define different embryonic progenitor pools that are destined to generate two molecularly and electrophysiologically distinct subclasses of mature MeA inhibitory output neurons. We have further shown that MeA Dbx1-lineage and Foxp2-lineage neurons respond in a sex and lineage-specific manner to aggressive, defensive, or mating cues (Lischinsky et al, 2017). Understanding both sex and lineage-specific differences in neuronal biophysical properties is a critical step to ultimately understand how different neuronal populations in the male and female MeA processes sensory information for appropriate behavioral outputs.…”
Section: Introductionmentioning
confidence: 78%
“…The medial amygdala (MeA) is a major brain nucleus for distinguishing olfactory cues that drive innate behaviors such as mating, territorial defense, predator avoidance and maternal and paternal care (McCarthy and Arnold, 2011;Sokolowski and Corbin, 2012;Bergan et al, 2014;Yang and Shah, 2014;Li and Dulac, 2018). In both females and males, the MeA responds to both sex-specific (e.g., opposite sex odors) and non-sex-specific (e.g., predator odor) cues (Choi et al, 2005;Wu et al, 2009;Root et al, 2014;Carvalho et al, 2015;Unger et al, 2015;Bayless and Shah, 2016;Lischinsky et al, 2017;Yao et al, 2017). In addition, MeA neurons in females and males display differences in a number of anatomic, morphologic, and molecular characteristics, including cell number, dendritic complexity, and gene expression patterns (Cooke et al, 1999;Cooke and Woolley, 2005;Johnson et al, 2008;Morris et al, 2008;Wu et al, 2009Wu et al, , 2017Unger et al, 2015;Chen et al, 2019;Gegenhuber and Tollkuhn, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, complexes including FOXP2 with nuclear receptors might be promising therapeutic candidates. For instance estrogen and androgen receptors colocalize with Foxp2 in mouse amygdala [ 104 ], and rat brain [ 105 ]. Whether this co-localization translates into real complexes remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Further functional links between FOXP2 and cancer through dysregulation of other signaling processes may warrant examination. Among those we speculate that estrogen/androgen pathways relate FOXP2 and oncogenesis [ 104 , 105 ] (see section 5.1.5 . Prostate cancer).…”
Section: Introductionmentioning
confidence: 99%